Draft genome sequence of Yersinia pseudotuberculosis isolated from a wild rat in Japan - Okutani, Akiko; Taira, Masakatsu; Iida, Shun; Park, Eun-Sil; Tokuyoshi, Mikuni; Watari, Yuya; Suzuki, Tadaki; Maeda, Ken (Microbiology resource announcements, 2024)
We report a draft genome sequence of isolated from the spleen of a wild rat from Mikura-shima Island, Japan. The bacterium was identified as serotype O:4b using PCR-based O-genotyping. These genomic data provide insights into the pathogenic potential of this strain in spontaneous outbreaks among wild animals.